Redox‐Induced Oxidative C−C Bond Cleavage of 2, 2′‐Pyridil in Diruthenium Complexes. Issue 41 (28th June 2019) - Khan, Farheen Fatima; Sobottka, Sebastian; Sarkar, Biprajit; Lahiri, Goutam Kumar
Abstract: In the recent years, there has been an emerging research interest in the domain of C−C bond‐cleavage reactions. The present contribution deals with the redox‐mediated dioxygen activation and C−C bond cleavage in a diruthenium complex [(acac)2 Ru II (μ‐L1)Ru II (acac)2 ], 1 (acac=acetylacetonate) incorporating 2, 2′‐pyridil (L1) as the bridging ligand. The above process leads to a C−C‐cleaved monomeric product [(acac)2 Ru III (pic − )], 2 (pic − =piconilate). Intriguingly, similar diastereomeric complexes [(acac)2 Ru II (μ‐L2)Ru II (acac)2 ], meso (ΔΛ):3 a and rac (ΔΔ/ΛΛ):3 b, involving an analogous diimine bridge (L2= N 1, N 2‐diphenyl‐1, 2‐di(pyridin‐2‐yl)ethane‐1, 2‐diimine), were stable towards such oxidative transformations. Electrochemical and spectroelectrochemical studies, in combination, establish the potential non‐innocent feature of the 2, 2′‐Pyridil (L1) and its derivative (L2) both in oxidation and reduction processes. Additionally, theoretical calculations have been employed to verify the redox states and their behavior. Furthermore, transition state (TS) calculations at the M06L/6‐31G*/LANL2DZ level of theory together with detailed kinetic studies outline a putative mechanism for the selective transformation of1 →2 involving the formation of an intermediate bearing peroxide linkage to complex1 . Abstract : Redox induced transformation : 2, 2′‐Pyridil and its derivative ( N 1, N 2‐diphenyl‐1, 2‐di(pyridin‐2‐yl)ethane‐1, 2‐diimine) have been explored as bridging ligands in diruthenium frameworks. The bridging ligands are potentially non‐innocent and a differing response is observed amongst the two dimeric ruthenium complexes on interaction with atmospheric oxygen.